Con/artist : the life and crimes of the world's greatest art forger - Tetro, Tony; Ambrosi, Giampiero (Hachette Books, 2022)
"The world's most renowned art forger reveals the secrets behind his decades of painting like the masters--exposing an art world that is far more corrupt than we ever knew while providing an art history lesson wrapped in sex, drugs, and Caravaggio"--Dust jacket flap.